Die Prekarisierungsgesellschaft - Marchart, Oliver (Gesellschaft der Unterschiede, 2013)
Society appears to us today in the flickering light of instability. It has not just been since the financial crisis that matters related to working and living conditions have proved themselves to be precarious. The author introduces the most important economic and sociological theories of precarization, and demonstrates that precarity has seized society in its entirety. We live in the society of precarity. But what can be drawn from this? Marchart describes contemporary social protests and their demands. He investigates their democratic and political implications and works towards a social theory of the conflict and of its contingencies.